2016
DOI: 10.1155/2016/2405624
|View full text |Cite
|
Sign up to set email alerts
|

How Does Environmental Regulation Affect Industrial Transformation? A Study Based on the Methodology of Policy Simulation

Abstract: The difference of factor input structure determines different response to environmental regulation. This paper constructs a theoretical model including environmental regulation, factor input structure, and industrial transformation and conducts a policy simulation based on the difference of influencing mechanism of environmental regulation considering industrial heterogeneity. The findings show that the impact of environmental regulation on industrial transformation presents comparison of distortion effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…Environmental regulation expenditures have statistically significant effects on the probabilities of a company's capacity moving to a larger company-size category, so industry structure is affected by environmental regulation [41]. However, the impact of environmental regulation on industrial transformation presented a comparison of distortion effect of resource allocation and technology effect [42]. Environmental regulation will promote industrial transformation when technology effect of environmental regulation is stronger than distortion effect of resource allocation [42].…”
Section: Environmental Regulation Industrial Structure and Carbon Emissionsmentioning
confidence: 99%
“…Environmental regulation expenditures have statistically significant effects on the probabilities of a company's capacity moving to a larger company-size category, so industry structure is affected by environmental regulation [41]. However, the impact of environmental regulation on industrial transformation presented a comparison of distortion effect of resource allocation and technology effect [42]. Environmental regulation will promote industrial transformation when technology effect of environmental regulation is stronger than distortion effect of resource allocation [42].…”
Section: Environmental Regulation Industrial Structure and Carbon Emissionsmentioning
confidence: 99%
“…Moreover, there are great differences in the description of ERs, industrial redistribution, FDI, and other indicators [17]. Some have pointed out that enterprises would adopt different strategies in the face of strict ERs, and some enterprises would close their factories rather than choose another site [5,6,39]. Similarly, researchers have tended to adopt a 'black or white' attitude in the verification process, which implies ignorance or negation of other hypotheses [3,6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Resource endowment selects the proportion of the number of mining employees to the total number of local employees to reflect the abundance of resources [64]. 5 Capital factors-Neoclassical trade theory emphasizes that when the factor endowments of two countries are different, the product price of the region with abundant factor endowments is lower, which makes it easier to gain profits in international trade. This can also reflect the important role of capital in industrial distribution.…”
Section: Spatial Panel Regression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars have demonstrated the "Porter Hypothesis" from different premises (Cole et al, 2005;Ramanathan et al, 2010;Hou et al, 2018;Yu ang Wang, 2020), For example, Burton et al (2011) studied the pulp and paper industry through environmental regulation factors, and concluded that environmental regulation has a significant role in promoting the growth of such enterprises and significantly improving the level of structural optimization of the industry. Liu et al (2016) constructed a theoretical model of the impact of environmental regulation on the upgrading of industrial structure. They pointed out that if the technical effect of environmental regulation is higher than the distortion effect of resource allocation, environmental regulation will promote the transformation and upgrading of industrial structure.…”
Section: Literature Reviewmentioning
confidence: 99%